معايير العذر الطارئ في الفقه الإسلامي وتطبيقاته على جائحة كوفيد-19 - الغنانيم، قذافي عزات عبدالهادي (جامعة الجزائر - كلية العلوم الإسلامية, 2021)
تناول البحث دراسة موضوع "معايير العذر الطارئ في الفقه الإسلامي وتطبيقاته على جائحة كوفيد19" من حيث المفهوم، والحكم، والتطبيق، دراسة تأصيلية وفق أصول، وقواعد العذر الطارئ عند الفقهاء، ووقف الباحث في المبحث الأول منه على مفاهيم الدراسة للعذر الطارئ، وكوفيدا-19، وفي المبحث الثاني على معايير العذر الطارئ، من المعيار المادي، والشرعي، والشخصي، وموقف الفقهاء من كل معيار، وفي الثالث على تطبيق هذه المعايير على فايروس كوفيد-19، وتحرير مناطات تحققه وفق هذه المعايير؛ للنظر في مدى صلاحيته للتعذر في الالتزامات التعاقدية، وترتب الأحكام الخاصة به. واعتمد الباحث على المنهج التحليلي بشكل رئيس في معالجة جميع مسائل البحث الواردة فيه، وذلك ابتداء من تحرير معايير العذر الطارئ من التطبيقات الفقهية الواردة في باب الإجارة، وما يصلح منها للتعذر، ومن ثم تطبيقها على فايروس كوفيد-19. وتوصل الباحث إلى جملة من النتائج التي تظهر أن التعذر متحقق في حالة الإصابة بالفيروس، أو انتشاره على مستوى المعيار المادي، والشخصي.
The research studied the subject of "Criteria for urgent excuse in Islamic jurisprudence And its application on the COVID -19 pandemic" in terms of concept, judgment, and application, a rooting study according to the origins, and the rules of urgent excuse at jurists, and the researcher stood in the first division on the study concepts for the urgent excuse, and COVID-19. In the second part the criteria of urgent excuse, from the material, legal and personal criterion, and the jurists opinion on each criterion, and in the third to apply these standards to the Virus of COVID-19, in addition to liberalize the regulations achieved in accordance with these criteria, to consider the validity of its excuse on the contractual obligations, and classifying its provisions . The researcher relied mainly on the analytical approach in addressing all the research contained issues, starting with the liberalization of the criteria of urgent excuse from the jurisprudence applications contained in AL-IJARAH section, and what is suitable for the immeasurability, and then applying them to the COVID-19 Virus. The researcher came up with a number of results that show the excuse is achieved in the case of virus infection, or its spread at the level of the physical and personal criterion.
Keywords: النوازل الفقهية -- الطوارئ الصحية -- فيروس كورونا "كوفيد-19" -- الأحكام الشرعية